2020
DOI: 10.21873/anticanres.14169
|View full text |Cite
|
Sign up to set email alerts
|

Textbook Outcomes Among Patients Undergoing Retroperitoneal Sarcoma Resection

Abstract: Background/Aim: Recently, the concept of textbook outcome (TO) has emerged as a novel effort to develop a benchmark that reflects multiple domains of quality. The aims of the current study were to define TO for retroperitoneal sarcoma (RPS), evaluate the relationship of TO with hospital volume and assess the association of TO with overall survival. Patients and Methods: Patients who underwent resection for RPS diagnosed between 2004 and 2015 were identified in the National Cancer Database. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
13
1
Order By: Relevance
“…In the current study, patients with a TO experienced a median OS that was approximately two‐fold longer than those who failed to achieve a TO; this association was maintained even as patients were stratified by histology or tumor recurrence status. These findings are consistent with previous studies highlighting the association between perioperative complications and long‐term cancer outcomes 31,46‐48 . Therefore, future efforts directed towards improving efforts to identify modifiable preoperative risk factors for postoperative complications will in turn improve the rate of TO following RPS resection is critical not only for improving short‐term quality of surgery but also long‐term survival rates for these patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, patients with a TO experienced a median OS that was approximately two‐fold longer than those who failed to achieve a TO; this association was maintained even as patients were stratified by histology or tumor recurrence status. These findings are consistent with previous studies highlighting the association between perioperative complications and long‐term cancer outcomes 31,46‐48 . Therefore, future efforts directed towards improving efforts to identify modifiable preoperative risk factors for postoperative complications will in turn improve the rate of TO following RPS resection is critical not only for improving short‐term quality of surgery but also long‐term survival rates for these patients.…”
Section: Discussionsupporting
confidence: 90%
“…Remarkably, these results are not too dissimilar to rates of TO among other complex surgical oncology procedures reported in the literature: esophagectomy for cancer (29.7%), 25 gastrectomy for cancer (22% to 32.1%), 25,26 major pancreatic resection (16.8% to 67.4%) 7,18,22,24 major liver resection (33.3%), 7 and resection for intrahepatic cholangiocarcinoma (25.5%) 21 . In contrast to the current cohort findings, while investigating patients undergoing RPS using the National Cancer Database, Moris et al 31 found a much higher rate of TO (54.0%). This observed difference is likely explained by the less stringent TO criteria definition put forth by Moris et al which lacks accounting for complications, receipt of transfusions, reoperations, readmissions beyond the 30‐day mark, and nonhome discharge.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…These is contrary to findings of other cancers. In patients with retroperionteal sarcomas, Moris et al 25 found that high‐volume centers were more likely to be associated with a TO in patients undergoing treatment for retroperitoneal sarcoma. Our findings are interesting as it suggests that these are independent factors contributing to survival in patients with STS‐E.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical advantage of the TO concept is that it may provide an estimation of quality of care by surgeons and patients, and it can allow the classification of hospitals and institutions as experts based on their performance. To date, TOs have been developed for several gastrointestinal malignancies—including esophagogastric and hepatobiliary malignancies 18,21‐25 . These same metrics have not been established for STS‐E.…”
Section: Introductionmentioning
confidence: 99%